2006
DOI: 10.1016/j.ejcts.2006.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Administration of C1-esterase inhibitor during emergency coronary artery bypass surgery in acute ST-elevation myocardial infarction☆

Abstract: C1-INH administration in emergency CABG with acute STEMI is safe and effective to inhibit complement activation and may reduce myocardial ischemia-reperfusion injury as measured by cTnI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Prior studies conducted on patients with acute myocardial infarction have shown that treatment with intravenous C1-INH may reduce myocardial injury. 30,31 Based on our findings it can be assumed that supplementation with C1-INH during the postoperative period might be beneficial in the prevention of restenosis in patients with CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies conducted on patients with acute myocardial infarction have shown that treatment with intravenous C1-INH may reduce myocardial injury. 30,31 Based on our findings it can be assumed that supplementation with C1-INH during the postoperative period might be beneficial in the prevention of restenosis in patients with CEA.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, C1-inhibitor half-life was calculated to be Ϸ35 hours, and administration of C1-inhibitor (40 IU/kg) to patients during bypass surgery after myocardial infarction has been shown to be beneficial, without adverse effects or complications. 47 In a porcine model, C1-inhibitor at 40 IU/kg was effective and had no associated adverse effects, but used at a higher dose (100 and 200 IU/kg), it provoked severe side effects and coagulation disorders. 48 In mice, however, treatment with the C1-inhibitor (at 15 IU per mouse, which corresponds to Ϸ400 IU/kg) was well-tolerated, and no adverse effects, infections, or bleeding disorders were observed.…”
Section: Shagdarsuren Et Al C1-esterase Inhibitor Reduces Neointima Fmentioning
confidence: 99%
“…However, despite these profound experimental data, the only available clinical trial addressing the role of sCR1 in ischemia-reperfusion injury yielded disappointing therapeutic results [128]. In contrast, the efficacy of C1-Esterase inhibitor (C1-INH) in preventing reperfusion injury has been shown experimentally in rats [129] and pigs [83,130] as well as clinically [131], where application of C1-INH in patients with coronary bypass surgery in acute ST-elevation myocardial infarction resulted in reduced myocardial reperfusion injury [132,133] and improved cardiac function [134].…”
Section: Contemporary Treatment Strategiesmentioning
confidence: 99%